Inferior Vena Cava Filters—Current Role and Controversies - Kapoor, Harit; Raissi, Driss (Journal of Clinical Interventional Radiology ISVIR, 2019)
Inferior vena cava filters (IVCFs) remain an indispensable part of an interventionalist's toolbox. Increased recognition of filter-related complications, largely from off-label use and casual approach to filter retrieval, has led to tremendous uncertainty surrounding their use. More stringent regulations on their use and development of newer and safer anticoagulants are gradually changing their role in the management of venous thromboembolism. Herein, the authors review the current role of IVCFs, indications for their use and retrieval, as well as filter-related complications.
Keywords: inferior vena cava filter; venous thromboembolism; retrievable filter; anticoagulation; temporary filter; optional filter; superior vena cava filter